Visualisasi Bibliometrik Penelitian Bidang Ilmu Kegempaan di Indonesia Berbasis Data Scopus Tahun 1988-2018 - Royani, Yupi; Tupan, Tupan; Kusumaningrum, Dwiatri (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2019)
Penelitian ini bertujuan untuk melihat; 1) pertumbuhan publikasi ilmiah tentang gempa di Indonesia, 2) jurnal inti publikasi ilmiah ilmu tentang gempa di Indonesia, 3) produktivitas dan kolaborasi peneliti ilmu tentang gempa, 4) jumlah publikasi ilmu kegempaan berdasarkan afiliasi/lembaga, 5) jumlah publikasi berdasarkan negara, 6) jumlah publikasi berdasarkan tipe dokumen, 7) jumlah publikasi berdasarkan subjek, 8) peta perkembangan tentang gempa melalui kluster kata kunci. Data diperolah penelitian melalui database Scopus yang terbit pada periode tahun 1988-2018. Analisis data menggunakan software VOSviewer. Hasil penelitian menunjukkan bahwa Geophysical Research Letters, Journal of Volcanology and Geothermal Research, IOP Conference Series Earth and Environmental Science, dan Geophysical Journal International banyak mempublikasikan kajian tentang gempa. Subjek yang terbanyak diteliti adalah Earth and Planetary Sciences, Engineering, Energy, Environmental Science, dan Physics and Astronomy. Tren penelitian terbanyak masalah seismology, seismic wave, seismic data, geophysics dan mathematical model, Indonesia, Asia, Eurasia, tectonics dan eartquake rupture, volcanoes dan tremor. ABSTRACT: This study aims to describe; 1) growth of scientific publications on earthquakes in Indonesia, 2) core journal of scientific publications on earthquake sciences in Indonesia, 3) productivity and collaboration of earthquake researchers, 4) number of seismic science publications based on affiliation/institutions, 5) number of publications by country, 6) number of publications based on document type, 7) number of publications based on subjects, 8) map of developments on earthquakes through keyword clustering based on VOSviewer software. The data were gathered through the Scopus database from the period of time 1988-2018. The data was analyzed by using VOSviewer. The study found that most earthquakes publication was published in Geophysical Research Letters, Journal of Volcanology and Geothermal Research, IOP Conference Series Earth and Environmental Science, and Geophysical Journal International. The most studied subjects were Earth and Planetary Sciences, then followed by Engineering, Energy, Environmental Science, and Physics and Astronomy. From bibliometric visualization shows that the most research trends are problems of seismology, seismic wave, seismic data, geophysics, and mathematical models, Indonesia, Asia, Eurasia, tectonics and earthquake rupture, volcanoes and tremors.